Enhancing Parental Psychological Well-Being in Autism: The Role of Social Support and Religiosity - Fatimah, Siti; Fitriati, Sulivan (KnE Social Sciences, 2025)
This study examines the influence of social support on psychological well-being of parents with ASD children, with the influence relationship being direct and through the role of religiosity as a mediator. This study uses a quantitative approach through data collection in the form of questionnaires which include three primary instruments: the Social Support Scale, the Religiosity Scale, and the Psychological Well-Being Scale. A total of 238 respondents who are parents with ASD children participated in this study. Data analysis is through Structural Equation Modeling (SEM) method. The results indicate that social support has a significant and direct effect on the psychological well-being of parents. Additionally, religiosity also mediates the relationship between social support and psychological well-being. In this case, social support fosters a sense of acceptance, reduces emotional burdens, and increases self-efficacy, while religiosity helps parents find meaning in the caregiving experience, providing emotional and mental strength. The synergistic combination of these two factors significantly enhance the psychological well-being of parents with ASD children. The findings of this study highlight the importance of interventions which target strengthening social support and religiosity to improve the psychological well-being of parents with ASD children.